The Influence of Giant Snakes Ladders Game "UTANG SASA" on the Knowledge and Attitude of Fruit and Vegetables Consumption of Children at Sidorahayu State Elementary School 2, Wagir, Malang - Christabel Engelberta; Handy Lala; Sugianto Hadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The giant ladder snake game is an educational and attractive game that can be used to influence the knowledge and attitudes of schoolchildren in the consumption of fruit and vegetables. Objective: This study aims to analyze the influence of the game Giant Ladder Snake on children in SDN 2 Sidorahayu on knowledge and attitudes about eating fruit and vegetables. Method: The study uses a pre-experimental design of a group pre-test-posttest carried out in February 2024 on 33 SDN 2 Sidorahayu, Wagir students. This education was conducted for two weeks with interventions once a week. The data collected is characteristic data, knowledge, and attitudes measured using a questionnaire. Data analysis is univariate and bivariate. Bivariate analysis using paired t-test or Wilcoxon sign rank test with ?=0,05 Result: The results of the study obtained a difference in knowledge after education with an average score of almost 85,76 compared to before education a small part 40,61. Whereas for the value of attitude, there is a difference in attitudes after giving education with the average score of mostly 65,76 before education mostly 57,82.The obtained probability value p-value 0,000 < 0.05 indicates that H1 accepted means there is an influence of the media game snake giant ladder on the knowledge and attitude of consumption fruit and vegetables at SDN 2 Sidorahayu, Wagir. Conclusion: Consequently, it can be said that the game Giant Ladder Snake has a media influence on students at SDN 2 Sidorahayu, Wagir, on their knowledge and attitudes toward the eating of fruits and vegetables.